Increased grassland arthropod production with mammalian herbivory and eutrophication: a test of mediation pathways. Issue 12 (8th November 2017) - Lind, Eric M.; La Pierre, Kimberly J.; Seabloom, Eric W.; Alberti, Juan; Iribarne, Oscar; Firn, Jennifer; Gruner, Daniel S.; Kay, Adam D.; Pascal, Jesus; Wright, Justin P.; Yang, Louie; Borer, Elizabeth T.
Abstract: Increases in nutrient availability and alterations to mammalian herbivore communities are a hallmark of the Anthropocene, with consequences for the primary producer communities in many ecosystems. While progress has advanced understanding of plant community responses to these perturbations, the consequences for energy flow to higher trophic levels in the form of secondary production are less well understood. We quantified arthropod biomass after manipulating soil nutrient availability and wild mammalian herbivory, using identical methods across 13 temperate grasslands. Of experimental increases in nitrogen, phosphorus, and potassium, only treatments including nitrogen resulted in significantly increased arthropod biomass. Wild mammalian herbivore removal had a marginal, negative effect on arthropod biomass, with no interaction with nutrient availability. Path analysis including all sites implicated nutrient content of the primary producers as a driver of increased arthropod mean size, which we confirmed using 10 sites for which we had foliar nutrient data. Plant biomass and physical structure mediated the increase in arthropod abundance, while the nitrogen treatments accounted for additional variation not explained by our measured plant variables. The mean size of arthropod individuals was 2.5 times more influential on the plot‐level total arthropod biomass than was the number of individuals. The eutrophication of grasslands through human activity, especially nitrogen deposition, thus may contribute to higher production of arthropod consumers through increases in nutrient availability across trophic levels.